Low molecular-weight gel fraction of Aloe vera exhibits gastroprotection by inducing matrix metalloproteinase-9 inhibitory activity in alcohol-induced acute gastric lesion tissues - Chul-Hong Park; Hyeong-U Son; Chi-Yeol Yoo; Sang-Han Lee (Taylor & Francis Group, 2017)
Context: Aloe has been used for the prevention and cure of various diseases and symptoms including burns, injuries, oedema and pain. Objective: This study determines the specific inhibitory activity of matrix metalloproteinase (MMP)-9 induced by the low molecular-weight gel fraction of Aloe vera (L.) Burm.f. (lgfAv) on alcohol-induced acute gastric lesions. Materials and methods: We examined the protective effects of oral (p.o.) administration of lgfAv (molecular weight cutoff <50.0 kDa, 150.0 mg/kg body weight) in a Balb/c mouse model of alcohol-induced acute gastritis for 1 h exposure. By measuring ulcer index, we compared the antiulcerative activity of the fraction. mRNA expression and immunohistochemical analysis of various biomarkers were performed. Results: The lgfAv-treated mice exhibited drastically fewer ulcer lesions than the untreated control mice did. It featured that lgfAv lessened the ulcer lesions than their relevant controls. Moreover, the transcriptional level of MMP-9 was completely alleviated by lgfAv treatment in alcohol-treated gastritis-induced mice. Discussion: The transcriptional level of MMP-9 was significantly alleviated by lgfAv treatment of the model. However, reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemistry experiments revealed that lgfAv treatment in mucosal tissues had the potential to inhibit the mRNA and protein expression levels of MMP-9, respectively. The protein expression of MMP-9 was closely associated with lgfAv-induced gastroprotection against alcohol-induced gastric lesions. Conclusions: The present findings suggest that lgfAv has the potential to alleviate alcohol-induced acute gastric lesions, which is mediated in part, mainly by the suppression of the mRNA expression of MMP-9.